RELATIONSHIP BETWEEN NLR, CRP AND D-DIMER LEVEL TO DISEASE SEVERITY IN COVID-19 PATIENTS HOSPITALIZED IN WANGAYA PUBLIC HOSPITAL - Wayan, Sunardiasih (E-Jurnal Medika Udayana, 2022)
Abstract  Coronavirus disease 19 (COVID-19) is a contagious disease caused by  Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus. The virus originated from the Coronaviridae family and is responsible for acute atypical respiratory disease that started in Wuhan, Hubei Province, China. Since it was declared as pandemic by WHO on March 11 2020, COVID-19 infection has become a big threat for human health because this disease consumes many health care resources. The increasing cases and death in Indonesia dramatically occured in June 2021. Increasing case numbers dramatically lead to increased health care resources, therefore disease severity evaluation becomes important in situations where resource is limited during this pandemic. The aim of this research is to know the relationship between NLR, CRP level, and D-dimer toward disease severity of COVID-19 patients. This research is observational analytic with retrospective design in confirmed  COVID-19 patients (rRT-PCR method) that also underwent complete laboratorium examination. This study used 80 samples that were hospitalized during the period June until August 2021 in Wangaya Public Hospital Denpasar. The sample of patients with severe grades then compared with non-severe grades. From the results of the analysis, the P values ??of the NLR were <0.001, CRP <0.001, and D-dimer 0.004, so there were significant differences in NLR, CRP and D-dimer levels in patients with severe and non-severe disease severity. Keywords : COVID-19, NLR, CRP, D-dimer